Autobus Linkego jako parodia PRL. Studium intertekstualne - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
Marek Hendrykowski’s study is concerned with the close-reading analysis and interpretation of the Autobus (1955–1961) oil on canvas painted by Bronisław Wojciech Linke. This masterpiece of Polish peinture of the 1950s is deeply related to history and conditions of human life in Poland and other East European countries after World War II where everyday life is based on ideology imposed on society. Linke’s peinture gives emblematic ironic image of it created as an anti-social realist protest based on paradigm of Polish culture and art of the period.